Dance for weightloss with Patricia Moreno [videorecording (DVD)]. (Gaiam, 2007)
Teaches cardio dance moves that slim, tone and strengthen your entire body. Gives easy-to-follow instructions while going through heart-pumping, calorie-burning dance workouts that will help you lose weight quickly.